Kemampuan Pedagogical Content Knowledge (PCK) Guru Matematika SMP Negeri 1 Mojogedang Dalam Penyusunan RPP - Purwadi, Hendi; , Muhammad Noor Kholid, S.Pd, M.Pd (2017)
Hendi Purwadi / A410130064. Ability Of Pedagogical Content Knowledge (PCK) Teacher Of SMP Negeri Teacher 1 Mojogedang In RPP Preparation. Essay. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. May, 2017. Teachers are an important part of an education. The purpose of this study is to determine the ability of Pedagogic Content Knowledge (PCK) Mathematics Teachers SMP Negeri 1 Mojogedang in preparing the RPP academic year 2016/2017. The type of this research is descriptive qualitative. The subject of this research is RPP Mathematics teacher of SMP Negeri 1 Mojogedang. The sampling technique in this study was random sampling by taking ten RPP randomly from each teacher. Data validity is done by interview technique. Based on the research that has been done, it is found that the ability of the Content Knowledge (CK) of teachers is not good (43.8%), the Pedagogic Knowledge (PK) of the teachers is good (74.1%), and Pedagogic Content Knowledge (PCK) (76.8%). So it can be concluded that the ability of Pedagogical Content Knowledge (PCK) of Mathematics teacher of SMP Negeri 1 Mojogedang based on Learning Plan (RPP) of academic year 2016/2017 is categorized well. With the enhancement of Pedagogical Content Knowledge (PCK) capabilities in the Teacher Implementation Plan (RPP), it is expected that the learning process in the classroom runs better. In order to obtain better teaching and learning outcomes. Keywords: Pedagogical Content Knowledge (PCK), Mathematics teacher, RPP